PHRASEOLOGY OF THE RUSSIAN LANGUAGE AS A REFLECTION OF THE LINGUISTIC PICTURE OF THE WORLD - Mirzaeva Klara Temirovna (Galaxy International Interdisciplinary Research Journal, 2023)
The history of the formation of phraseology is described, the main semantic and structural characteristics of phraseological units are listed. The importance of phraseology for the newly emerged branch of linguistics - linguoculturology is substantiated: phraseological units are able to accumulate the most important concepts of the linguistic picture of the world. In this article we have examined the phraseology of the Russian language in a narrow and broad sense, focused on its use in modernity.